Quantitative relationship between the amount of income and consumption in macroeconomic region (part 1) - Malakhovsky, Y.; Малаховський, Ю. В. (КНТУ, 2013)
This study aims to investigate the quantitative relationship between the level of production, actual income and consumption in Ukraine. For greater clarity, the individual figures are compared with data of other countries. The research based on a dual approach to the consideration of GDP as the market price of domestically produced goods and services in terms of income and expenses. This approach provides the possibility to produce consistent estimates of consumption of economic resources of the country, to study the structure of consumption in the context of separate institutional units. У публікації поставлено мету дослідити кількісні співвідношення між обсягами виробництва, формування доходів і споживання в Україні. Для більшої наочності окремі показники порівнюються з аналогічними для інших країн. Дослідження базуються на вивченні валового внутрішнього продукту, як матеріальної основи споживання, з точки зору систем формування доходів і здійснення витрат. Такий підхід забезпечує можливість отримувати узгоджені оцінки рівня поточного споживання економічних ресурсів країни, вивчати його структуру у розрізі окремих інституційних одиниць.
Кількісний аналіз зв’язків між обсягами доходів і споживання в макроекономічному регіоні
Keywords: final consumption expenditure; actual final consumption; ratio between income and consumption; methods of calculating the level of consumption; consumption multiplier; кінцеві споживчі витрати; фактичне кінцеве споживання; співвідношення між доходами і споживанням; методи розрахунку рівня споживання; мультиплікатор рівня споживання